A SYSTEMATIC LITERATURE REVIEW (SLR): ADAPTATION OF EDUCATORS' PROFESSIONALISM IN MARGINALISED AREAS TO DIGITAL CURRICULUM, TECHNOLOGY AND SOCIOCULTURAL DYNAMICS - Puput Tri Anggara; Farida Hanum; Serafin Wisni Septiarti (RADJA PUBLIKA, 2026)
The digital era has presented significant challenges and opportunities for teaching professionals, particularly in underserved areas. This study aims to examine the adaptation of educator professionalism to curriculum transformation, the integration of learning technology, and socio-cultural dynamics through a Systematic Literature Review (SLR) approach. The analysis process involved identifying, selecting, and synthesising 136 studies from the database, using specific inclusion criteria, over the past 10 years. The results indicate that teachers in marginalised areas face infrastructure constraints, digital literacy issues, a lack of ongoing training, and socio-cultural challenges that affect curriculum implementation, technology utilisation, and character building. The findings also reveal the role of teachers as mediators between the formal curriculum and local values, as well as the importance of adaptive policy support and learning communities to enhance learning effectiveness. This study provides critical insights into contextual professional development strategies that are responsive to regional heterogeneity, with implications for improving the quality of education in the digital era.